SISTEM INFORMASI PENJUALAN DAN PEMBELIAN PADA TOKO BAJU KANIA JAYA BERBASIS WEBSITE - Adam Denta Ramadhan (2023)
Until now, the sales information system in clothing stores is still predominantly manual and not computerized. This occurs when sales are recorded manually, including tracking sold items, managing inventory, and manually calculating prices by employees. Kania Jaya Clothing Store is a clothing store that offers a variety of affordable clothing for children and adults. Currently, Kania Jaya Clothing Store still relies on manual methods for sales and purchases. Additionally, transactions and inventory records are still maintained using paper notes. In this study, the author utilized the waterfall system design method and PIECES analysis with the concept of Data Flow Diagram (DFD) as a guide for programmers to develop a functioning system and proposals. The system is designed using PHP programming language and MySQL database. The research results indicate that the implementation of an information system in Kania Jaya Clothing Store makes it easier for administrators to store files and monitor real-time sales and purchases reports.